Scutellarin attenuates doxorubicin-induced oxidative stress, DNA damage, mitochondrial dysfunction, apoptosis and autophagy in H9c2 cells, cardiac fibroblasts and HUVECs. (August 2022) - Zhou, Li; Han, Yonglong; Yang, Quanjun; Xin, Bo; Chi, Mengyi; Huo, Yan; Guo, Cheng; Sun, Xipeng
Abstract: Studies on doxorubicin (DOX)-induced cardiotoxicity have mainly focused on cardiomyocytes (CMs), but it is unclear whether there are differences in the toxicity degree of DOX to CMs, cardiac fibroblasts (CFs) and endothelial cells (ECs). We used H9c2 cells, rat primary isolated CFs and human umbilical vein endothelial cells (HUVECs) to systematically research the cytotoxicity of DOX. Scutellarin (SCU) is a natural polyphenolic flavonoid that exerts a cardioprotective effect. In the present study, we explored the protective effects of SCU on DOX-induced cytotoxicity in H9c2 cells, CFs and HUVECs. The results showed that DOX decreased cell viability and increased the apoptosis rate, whereas DOX had a greater killing effect on H9c2 cells compared to CFs and HUVECs. DOX significantly elevated oxidative stress, but the malondialdehyde (MDA) levels in H9c2 cells were higher after DOX treatment. In all three cell types, DOX induced DNA damage and mitochondrial dysfunction, it activated apoptosis by activation of Bax/ Bcl-2 and it induced autophagy by inhibiting the Akt/ mTOR pathway. Pretreatment with different concentrations of SCU reversed these phenomena in a dose-dependent manner. Collectively, these results revealed that there were slight differences in DOX-induced cytotoxicity among H9c2 cells, CFs and HUVECs. Furthermore, the cardioprotective effect of SCU may be attributed to attenuation of DOX-induced oxidative stress, DNA damage, mitochondrial dysfunction, apoptosis and autophagy. Highlights: DOX-induced oxidative stress, DNA damage, mitochondrial dysfunction, apoptosis and autophagy in in three cardiac cell types. There were slight differences in DOX-induced cytotoxicity among H9c2 cells, cardiac fibroblasts and HUVECs. Scutellarin attenuates DOX-induced cytotoxicity.